INFRARED [FE II] EMISSION LINES FROM RADIATIVE ATOMIC SHOCKS - KOO, BON-CHUL; RAYMOND, JOHN C.; KIM, HYUN-JEONG (Journal of The Korean Astronomical Society, 2016)
[Fe II] emission lines are prominent in the infrared (IR) and important as diagnostic tools for radiative atomic shocks. We investigate the emission characteristics of [Fe II] lines using a shock code developed by Raymond (1979) with updated atomic parameters. We first review general characteristics of the IR [Fe II] emission lines from shocked gas, and derive their fluxes as a function of shock speed and ambient density. We have compiled available IR [Fe II] line observations of interstellar shocks and compare them to the ratios predicted from our model. The sample includes both young and old supernova remnants in the Galaxy and the Large Magellanic Cloud and several Herbig-Haro objects. We find that the observed ratios of the IR [Fe II] lines generally fall on our grid of shock models, but the ratios of some mid-IR lines, e.g., [Fe II] 35.35 µm/[Fe II] 25.99 µm, [Fe II] 5.340 µm/[Fe II] 25.99 µm, and [Fe II] 5.340 µm/[Fe II] 17.94 µm, are significantly offset from our model grid. We discuss possible explanations and conclude that while uncertainties in the shock modeling and the observations certainly exist, the uncertainty in atomic rates appears to be the major source of discrepancy.